2002
DOI: 10.1080/08958370290084494
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Risk Assessment of Durable Glass Fibers

Abstract: This article presents a quantitative risk assessment for the theoretical lifetime cancer risk from the manufacture and use of relatively durable synthetic glass fibers. More specifically, we estimate levels of exposure to respirable fibers or fiberlike structures of E-glass and C-glass that, assuming a working lifetime exposure, pose a theoretical lifetime cancer risk of not more than 1 per 100,000. For comparability with other risk assessments we define these levels as nonsignificant exposures. Nonsignificant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…They found an increased risk of respiratory system cancer in cohorts of MMMFexposed workers (Baccarelli et al, 2006;Greim et al, 2014;Shannon et al, 2005;Stone et al, 2004;Utell and Maxim, 2010). MMMFs could penetrate the epithelial cells and enter the lung interstitium (Fayerweather et al, 2002), which could induce persistent inflammation and lead to pulmonary fibrosis and respiratory cancer (Bottin et al, 2003). Studies have also shown that MMMFs could induce cancer in various experimental animals (Andersen et al, 2002); in addition, some in vitro toxicity studies have found that MMMFs exert cytotoxic and carcinogenic effects (Cui et al, 2018a;Rapisarda et al, 2015;Shibata et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…They found an increased risk of respiratory system cancer in cohorts of MMMFexposed workers (Baccarelli et al, 2006;Greim et al, 2014;Shannon et al, 2005;Stone et al, 2004;Utell and Maxim, 2010). MMMFs could penetrate the epithelial cells and enter the lung interstitium (Fayerweather et al, 2002), which could induce persistent inflammation and lead to pulmonary fibrosis and respiratory cancer (Bottin et al, 2003). Studies have also shown that MMMFs could induce cancer in various experimental animals (Andersen et al, 2002); in addition, some in vitro toxicity studies have found that MMMFs exert cytotoxic and carcinogenic effects (Cui et al, 2018a;Rapisarda et al, 2015;Shibata et al, 2007).…”
Section: Introductionmentioning
confidence: 99%